Rhyme and Meaning in Richard Crashaw - Rickey, Mary Ellen, 1929- (Book collections on Project MUSE., 1961)
Richard Crashaw's use of rhyme is one of the distinctive aspects of his poetic technique, and in the first systematic analysis of his rhyme craft, Mary Ellen Rickey concludes that he was keenly interested in rhyme as a technical device. She traces Crashaw's development of rhyme repetitions from the simple designs of his early epigrams and secular poems to the elaborate and irregular schemes of his mature verse.